Effect of Different Kefir Grain Starter Concentration on Yield, pH, CO2 Content, and Organoleptic Properties of Buffalo Milk Kefir - Lorentia Lydia Margareth; Nurwantoro Nurwantoro; Heni Rizqiati (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2020)
This research was investigated the effect of different kefir grain starter concentration on yield, pH, carbon dioxide (CO2) content, and organoleptic properties of buffalo milk kefir, and to investigated the ideal kefir grain concentration for good quality of kefir. Complete randomized design used in this research with 4 treatments and 5 replications in concentration 2.5, 5, 7.5, and 10% g/v kefir grain. Buffalo milk, kefir grain, Na2CO3 solution, 1% PP solution, pH meter, burette, and analytical balance were used in this research. The yield and pH of kefir was measured. Carbon dioxide (CO2) content was measured by Na2CO3 titration, while the organoleptic properties that included level of sourness, sour aroma, texture, and overall acceptance were done by 25 panelists. The results indicated that different kefir grain starter concentration significantly affected to the yield, pH, CO2 content, and organoleptic properties (p<0.05). The most optimal kefir grain concentration was 5% proved by yield 81.81%, pH value 4.20, CO2 content 0.43%, and proper organoleptic properties which were low level of sourness, acceptable aroma of kefir and texture. As conclusion, the concentration of grain relied on the kefir properties that may achieve in the optimum quality of kefir.